Sulphonation of synthetic rubber as an alternative membrane for proton exchange membrane fuel cell - Idibie, Christopher Avwoghokoghene (My University, 2010)
Synthesis and characterisation of PEM using aryl backbone commercial polystyrene-butadiene rubber (locally sourced) were carried out by sulphonation with chlorosulphonic acid, and assessed for its potential to serve as possible PEMFC application. The effect of weight of the polystyrene-butadiene rubber (PSBR), sulphonation time, stirring speed, concentration of sulphonation agent and sulphonation temperature on the degree of sulphonation (DS), ion exchange capacity (IEC) and viscosity of the resulting sulphonated material were investigated. Synthesized membranes were thus characterized by Fourier Transform Infra-red (FT-IR) and Proton Nuclear Magnetic Resonance (1HNMR) to confirm sulphonation. Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimentry (DSC) were used to verify the thermal stability of the membrane, while impedance spectroscopy was used to measure the proton conductivity of the membrane. The results obtained revealed that the weight of the rubber, sulphonation time, stirring speed, concentration of sulphonating agent and the sulphonation temperature affect the DS, IEC, viscosity, thermal stability and proton conductivity of the membrane, such that, sulphonation time of 24 hrs and acid concentration of 1.6 M/ml gave the best DS, with IEC ranging from 0.23 to 2.36 mmol/g. Conductivities were in the range of 10-3 – 10-2 S/cm. However, over 2 folds increase in ion exchange capacity and degree of sulphonation was achieved on the effect of temperature. The sulphonation kinetic of PSBR was studied in 0.0016 mol L-1 of chlorosulphonic acid where first-order kinetic model; without the effect of HCl and the effect of HCl were investigated. The reaction rate was found to obey the first-order model with the HCl produced having a desulphonation effect on the reaction. A predictive model Page iv developed is able to predict degree of sulphonation at different initial concentration of acid. The thermodynamic study showed that the reaction is non-spontaneous, and as temperature increases the reaction system experienced phase change from liquid to solid at temperature above 328 K. The DSC and TGA analysis showed that polystyrene-butadiene rubber is a thermo stable polymer for PEM fuel cell application with a glass transition temperature (Tg) of about 198oC. Porosity of the membrane and uptake of solvent per sulphonic groups at different thickness of membrane were also calculated. The porosity of the membrane to methanol increased with a decrease in membrane thickness and increased with an increase in methanol concentration. Based on the results obtained from the porosity of the membrane to methanol and methanol up take, it can be inferred that the membrane is less permeable to methanol than water. In comparism, the porosity of the synthesised membrane to methanol was less than that of Nafion® which was in the range of 0.40-0.51. The results also showed that water uptake increases as the thickness of the membrane decreases. However, the membrane was found to exhibit a moderately water absorption and desorption capacity. But considering the effect of temperature, the membrane will require proper humidification especially if the fuel cell where the membrane will be used will be operated above room temperature. The electrochemical activity test was performed on a single fuel cell fed with H2/O2 at room temperature. An open circuit voltage (OCV) of 718.75 mV was achieved with electrode 40 wt % loaded with catalyst, while a maximum power density of 73.68 mW/cm2 was recorded at 199.68 mA/cm2. The effect of degree of sulphonation resulted in 3.8 fold increase in performance of the cell potential. This study therefore shows that it is feasible to synthesize an alternative PEM to Nafion® that will be efficient for fuel cell application from a locally available polystyrene-butadiene rubber that is of commercial quantity.